Prolonged warm ischemia time increases mitogen-activated protein kinase activity and decreases perfusate cytokine levels in ex vivo rat liver machine perfusion - Kim, Joohyun; Hong, Seung-Keun; Yang, Yongqiang; Lee, Alice; Hoffmeister, Karin M.; Gantner, Benjamin N.; Park, Jong-In (Frontiers in Transplantation, 2023)
Machine perfusion is increasingly being utilized in liver transplantation in lieu of traditional cold static organ preservation. Nevertheless, better understanding of the molecular mechanisms underlying the ischemia-reperfusion injury (IRI) during ex vivo perfusion is necessary to improve the viability of liver grafts after transplantation using machine perfusion technology. Since key cellular signaling pathways involved in hepatic IRI may allow a chance for designing a promising approach to improve the clinical outcomes from this technology, we determined how warm ischemia time (WIT) during procurement affects the activity of mitogen-activated protein kinase (MAPK) and perfusate concentration of cytokines in an ex vivo rat liver machine perfusion model. Specifically, male Sprague-Dawley rats underwent in situ hepatic ischemia with varying WIT (0, 10, 20, 30 min, n=5 each), and subsequently 3 h of cold ischemia time and 2 h of machine perfusion prior to determining the degree of MAPK activation-phosphorylation and cytokine concentration in liver tissue and perfusates, respectively. Our data revealed a strong correlation between incremental WIT and a series of liver injury markers, and that prolonged WIT increases ERK1/2 and p54 JNK phosphorylation during machine perfusion. Notably, specific cytokine levels (MCP-1, MIP-2, GRO/KC, IL-10, and IL-5) were inversely correlated with the phosphorylation levels of ERK1/2, p38 MAPK, and p46/p54 JNK. These results suggest that MAPK activation, specifically ERK1/2 and p54 JNK phosphorylation, have potential as a biomarker for hepatic IRI pathophysiology during machine perfusion. Elucidation of their functional significance may lead to designing a novel strategy to increase the clinical benefit of machine perfusion.